Analisis Gerak Jump Serve Rivan Nurmulki pada Final SEA Games Thailand 2025 - Ahmad Salek Ma’arif; Nasuka (MAN Insan Cendekia Jambi, 2026)
This study examines Rivan Nurmulki’s jump serve motion during the men’s volleyball final at the 2025 SEA Games in Thailand. This study is based on the importance of the serve as an offensive technique in modern volleyball, as it can influence point scoring and the momentum of the match. The objective of the study is to compare the movement characteristics of failed and successful jump serves based on biomechanical indicators. The method used is quantitative descriptive, with data consisting of match recordings from YouTube. Analysis was conducted using Kinovea to measure the approach distance, stride length, body angle, jump height, ball reach height, and ball speed. The results of the study indicate that successful jump serves exhibit more optimal movement patterns compared to failed serves. For successful serves, the approach distance was 471.75 cm, the first step was 107.46 cm, the second step was 139.85 cm, the jump height was 123.96 cm, the ball reach height was 387.89 cm, and the ball speed was 16.73 m/s. The success of the jump serve is influenced by the coordination of the approach, takeoff, body position, point of impact, and arm swing, making it a benchmark for evaluation by coaches and athletes.